Level of Islamic High Schools Students' Chemistry Literacy - Mubarak, Syarifatul; Mizriaty, Alfina; Mujakir, Mujakir; Bilad, Muhammad Roil (Jurnal Tadris Kimiya, 2025)
Chemical literacy is a core construct in chemistry education, reflecting students’ ability to understand chemical concepts, coordinate macroscopic, sub-microscopic, and symbolic representations, and apply chemistry knowledge meaningfully. In Indonesia, persistent regional disparities in educational quality remain a challenge, particularly in provinces with lower human development indicators. West Nusa Tenggara has recently been identified as a region with relatively high general illiteracy rates, raising concerns about students’ chemical literacy at the upper secondary level. This study aimed to investigate the chemical literacy levels of Grade XI students enrolled in State Islamic Senior High Schools across West Nusa Tenggara. A quantitative research design was employed involving 654 students selected through multi-stage cluster sampling based on regional Human Development Index classifications. Data were collected using the Chemical Literacy Instrument (CLI), a validated three-tier diagnostic assessment designed to capture students’ conceptual understanding and reasoning across macroscopic, sub-microscopic, and symbolic levels. The instrument consisted of ten items covering core chemistry topics commonly taught in senior secondary education. Descriptive statistical analyses were conducted to categorize students’ chemical literacy into nominal, functional, conceptual, and scientific illiteracy levels. The results reveal critically low levels of chemical literacy. Only 12.62% of students demonstrated nominal literacy, 9.16% reached the functional level, and merely 1.12% achieved conceptual literacy, while 77.10% of students were classified as scientifically illiterate. This study provides novel large-scale empirical evidence on chemical literacy in Islamic secondary education contexts within developing regions, highlighting persistent representational and conceptual gaps that remain underexplored in existing chemistry education research. The findings underscore the need for instructional approaches that explicitly support representational competence, diagnostic assessment, and conceptual integration to strengthen chemical literacy development in secondary chemistry education.